2022
DOI: 10.1038/s41598-022-23997-x
|View full text |Cite
|
Sign up to set email alerts
|

Allyl ether of mansonone G as a potential anticancer agent for colorectal cancer

Abstract: Mansonone G (MG), a 1,2-naphthoquinone isolated from the heartwood of Mansonia gagei Drumm, exhibited several pharmacological activities such as anti-bacterial, anti-estrogenic and anti-adipogenic effect. This study evaluated the cytotoxicity of MG and its derivatives as well as determined the mechanism(s) underlying the cytotoxic activity of the most potent MG derivative on two CRC cell lines, HCT-116 cells carrying p53 wild-type and HT-29 cells carrying p53 mutant. We found that MG and its derivatives could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Among them, the substructure #580 contains allyl ether fragments. Accumulating evidence has suggested that some allyl ether derivatives (e.g., CYP2E1 inhibitors and mansonone G) exert obvious cytotoxic efficacy against hepatocytes, astrocytes, and colon cancer cells. These findings indicated that the substructure #580 has the potential to cause cytotoxicity. According to the feature of substructure #301(1), it is found that #301(1) belongs to the α,β-unsaturated carbonyl compound.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the substructure #580 contains allyl ether fragments. Accumulating evidence has suggested that some allyl ether derivatives (e.g., CYP2E1 inhibitors and mansonone G) exert obvious cytotoxic efficacy against hepatocytes, astrocytes, and colon cancer cells. These findings indicated that the substructure #580 has the potential to cause cytotoxicity. According to the feature of substructure #301(1), it is found that #301(1) belongs to the α,β-unsaturated carbonyl compound.…”
Section: Resultsmentioning
confidence: 99%
“…The next day, the membrane was incubated with a secondary antibody for 1.5 hours at room temperature. Finally, protein bands were treated with ECL chemiluminescence reagent, exposed, and photographed [42] . Images were processed and analyzed for grayscale using PS and Image J software.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, protein bands were treated with ECL chemiluminescence reagent, exposed, and photographed. [42] Images were processed and analyzed for grayscale using PS and Image J software.…”
Section: Western Blot Assaymentioning
confidence: 99%